Synthesis and characterizations of hydrophilic pHEMA nanoparticles via inverse miniemulsion polymerization - Zalikha Ismail,; Noor Aniza Harun, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study highlights on the development of hydrophilic polymer nanoparticles prepared via inverse miniemulsion polymerization, a robust technique to prepare hydrophilic and aqueous-soluble polymeric nanoparticles. 2-hydroxyethyl methacrylate (HEMA) is excellent candidate for homo-polymerization due to its biocompatibility and biodegradability characteristic with high hydrophilicity properties. The influence of synthesis parameters including the effects of sonication time ranging from 10 - 30 min and sonication amplitude up to 60% towards the particles size and morphology of pHEMA nanoparticles are investigated. The formation of pHEMA nanoparticles are confirmed by Fourier Transform Infrared (FTIR). The morphology of polymer nanoparticles has been determined using Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). Dynamic light scattering (DLS) indicates the mean diameters of pHEMA nanoparticles were in a range of 100 – 200 nm. The hydrophilic polymer nanoparticles obtained are expected to facilitate in the fabrication of inorganic-polymer composite nanoparticles especially in biological applications.